Modifying routine emergency medical team introductory training to a virtual storytelling (talanoa) format for Pacific island countries and areas - Cook, Anthony T; Casey, Sean T; Noste, Erin (Western Pacific Surveillance and Response, 2024)
This article describes the development of an online, remote and interactive emergency medical team (EMT) training series to engage current and prospective Pacific EMT team members during the COVID-19 pandemic. This was done incorporating talanoa sessions. In many Pacific languages, talanoa means to tell a story or have a conversation.
Keywords: rapid response team; disasters; Pacific islands